2020
DOI: 10.3389/fbioe.2020.00054
|View full text |Cite
|
Sign up to set email alerts
|

LINC00346 Acts as a Competing Endogenous RNA Regulating Development of Hepatocellular Carcinoma via Modulating CDK1/CCNB1 Axis

Abstract: Hepatocellular carcinoma (HCC) is one of the important types of liver cancer. LncRNA is an important regulatory factor that regulates many biological processes such as tumor cells during tumorigenesis and metastasis. LINC00346 has been associated with various types of liver cancer, but its role and regulatory mechanism in HCC remain unclear. In our study, we found the LINC00356-miR-199a-3p-CDK1/CCNB1 axis through bioinformatics analysis. The expressions of LINC00356, miR-199a-3p, CDK1, and CCNB1 in HCC and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 36 publications
3
49
0
Order By: Relevance
“…Moreover, we proposed that FOXM1 directly bound to CCNB1 and recruited CBP/P300 to enhance the H3K27ac levels. Previous studies identified the oncogenic role of CCNB1 in different cancers, including hepatocellular carcinoma 15 and cervical cancer. 18 Also, CCNB1 represents a prognostic factor for overall survival and metastasis-free survival in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we proposed that FOXM1 directly bound to CCNB1 and recruited CBP/P300 to enhance the H3K27ac levels. Previous studies identified the oncogenic role of CCNB1 in different cancers, including hepatocellular carcinoma 15 and cervical cancer. 18 Also, CCNB1 represents a prognostic factor for overall survival and metastasis-free survival in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous lncRNAs, such as ubiquitin conjugating enzyme E2 R2-AS1 ( 34 ), colorectal neoplasia differentially expressed ( 35 ) and snail family transcriptional repressor 3-AS1 ( 36 ), are differentially expressed in HCC and are closely associated with clinicopathological factors and prognosis of patients with HCC ( 37 39 ). For instance, these lncRNAs participate in the regulation of various aggressive cellular features during hepatocarcinogenesis and cancer progression ( 40 42 ). Hence, identifying HCC-relevant lncRNAs, as well as understanding their detailed roles are critical for developing effective targets for the diagnosis, prognosis and therapy of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Zou Y, et al conducted a multi-omics analysis of CDK1, CCNB1 and CCNB2 and found that they are potential prognostic biomarkers and associated with immune cell in ltration in HCC [37]. The experimental version of the Jin J L, et al study con rmed LINC00346 could regulate LINC00346-miR-199a-3p-CDK1/CCNB1 Axis to in uence the progress of HCC [38]. CDC20, also known as cell division cycle 20, is an cell-cycle regulator required for the completion of mitosis and an activator of the anaphase-promoting complex/cyclostome (APC/C) in the cell cycle [39].…”
Section: Discussionmentioning
confidence: 99%